1, 4‐Diketones from Cross‐Conjugated Dienones: Potassium Permanganate‐Interrupted Nazarov Reaction. Issue 34 (3rd July 2015) - Kwon, Yonghoon; Schatz, Devon J.; West, Frederick G.
Abstract: A domino potassium permanganate‐interrupted Nazarov reaction to yield syn‐2, 3‐disubstituted 1, 4‐diketones via a decarbonylative cleavage of the Nazarov oxyallyl intermediate, believed to be without precedent, is presented. This process allows syn substituents to be established stereospecifically on the 2‐carbon bridge connecting the ketone carbonyl carbons, and the formation of one carbon–carbon and two carbon–oxygen bonds. Two carbon–carbon bonds are cleaved in this process. Abstract : Cut and paste with manganese and iron : A new example of interrupted Nazarov reaction is described, involving oxidative cleavage of the oxidocyclopentenyl intermediate to produce 1, 4‐diketones. Simple treatment of cross‐conjugated dienones with FeCl3 ⋅6 H2 O and KMnO4 at low temperature affords the products under convenient conditions.